Impact of storage temperatures on the quality of oven-dried black jelly mushroom, Auricularia nigricans (Agaricomycetes) - Mohammad Yusof, Siti Nurhuda; Raseetha, Siva; Sabaratnam, Vikineswary; Abdullah, Sumaiyah; Mohd Razali, Razifah; Bahar, Asrul (Begell House, 2022)
The aim of this study was to determine the effects of various storage temperatures (4, 25, and 35°C) on quality parameters and microbial counts of oven-dried black jelly mushroom (Auricularia nigricans) for a period of 60 days. The mushroom was dried using a cabinet dryer at 60°C for 24 h to a constant weight prior to storage. The water activity of oven-dried A. nigricans indicated a 96% increment (35°C) compared to 40% (4°C) after being stored for 60 days. Similarly, moisture content showed approximately 4-fold elevation at 35°C compared to a 2-fold increase at 4°C after 60 days. However, at the end of storage, total phenolic content underwent a 46% reduction for storage at 35°C compared to a 29% reduction at 4°C. Likewise, the ferric reducing antioxidant power was also reduced nearly 45% (35°C) compared to 40%(4°C). Microbial counts at 4°C were lower [6.40 log colony forming units (CFU)/g] compared to storage at 35°C (6.47 log CFU/g) after 60 days. Taken altogether, the best storage temperature for oven-dried black jelly mushroom was at 4°C.